2021
DOI: 10.18502/cmm.6.4.5437
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis: Literature review and retrospective report of 15 cases from Portugal

Abstract: Background and Purpose: Prevalence of mucormycosis is growing with the increase of the population at risk. Current recommendations for its management are mostly based on retrospective studies. 3 study aimed to present the cumulative experience of an Infectious Diseases Department from a Portuguese hospital in the management of mucormycosis and discuss the potential gaps in the diagnostic and therapeutic approaches of this infection. Materials and Methods: For the purposes of the study, the electronic hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 35 publications
(130 reference statements)
0
14
0
Order By: Relevance
“…A previous study confirmed the value of quantitative polymerase chain reaction (qPCR) in BAL regarding earlier diagnosis in cases of PM [ 34 ]. Many ongoing studies focusing on noninvasive methods, such as qPCR for the detection of circulating deoxyribonucleic acid (DNA) in blood (plasma or serum) or urine, are beginning to show the value of early diagnosis and early treatment [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study confirmed the value of quantitative polymerase chain reaction (qPCR) in BAL regarding earlier diagnosis in cases of PM [ 34 ]. Many ongoing studies focusing on noninvasive methods, such as qPCR for the detection of circulating deoxyribonucleic acid (DNA) in blood (plasma or serum) or urine, are beginning to show the value of early diagnosis and early treatment [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF can be a monomicrobial or polymicrobial disease. The most common etiological agents are bacteria such as Streptococcus pyogenes, however it can also be caused by fungi like those of the Mucorales order [3][4][5] . urine, leading to the added diagnosis of pneumonia and urinary tract infection.…”
Section: Introductionmentioning
confidence: 99%
“…Ceftazidime was stopped, and meropenem, clindamycin and vancomycin were initiated as prevention against methicillin-resistant S. aureus (MRSA) and gram-negative agents. We were not able to control the infection with medical They cause a rare and opportunistic fungal infection, named primary cutaneous mucormycosis [4,5] . Mucormycosis mostly affects immunocompromised hosts, and produces serious lesions with cutaneous necrosis, thrombosis and vascular invasion leading to systemic infection and a poor prognosis [4,5] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations